2004
DOI: 10.1016/j.jep.2004.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxation induced by common edible tropical plant extracts in isolated rat aorta and mesenteric vascular bed

Abstract: In this study, the vasodilatory actions of nine edible tropical plant extracts were investigated. Ipomoea batatas (sweet potato leaf), Piper betle (betel leaf), Anacardium occidentale (cashew leaf), Gynandropsis gynandra (maman leaf), Carica papaya (papaya leaf), and Mentha arvensis (mint leaf) extracts exhibited more than 50% relaxing effect on aortic ring preparations, while Piper betle and Cymbopogon citratus (lemongrass stalk) showed comparable vasorelaxation on isolated perfused mesenteric artery preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 17 publications
3
69
0
2
Order By: Relevance
“…They appear to be able to regulate antioxidant enzyme gene transcription and intercellular signalling cascades involved in the regulation of cell growth, inflammation and many other processes (Stangeland et al 2009). Additionally, several reports have demonstrated that the phenolic compounds exhibit antioxidant, anti-inflammatory, anti-mutagenic, anticarcinogenic, anti-bacterial properties (Negi et al 2008;Fresco et al 2010) (Jeong et al 2010; Jayakumar and Kanthimathi 2011) and possess hypotensive actions (Eno et al 2000) which are in agreement with their vasorelaxant effects (Runnie et al 2004). …”
Section: Discussionmentioning
confidence: 86%
“…They appear to be able to regulate antioxidant enzyme gene transcription and intercellular signalling cascades involved in the regulation of cell growth, inflammation and many other processes (Stangeland et al 2009). Additionally, several reports have demonstrated that the phenolic compounds exhibit antioxidant, anti-inflammatory, anti-mutagenic, anticarcinogenic, anti-bacterial properties (Negi et al 2008;Fresco et al 2010) (Jeong et al 2010; Jayakumar and Kanthimathi 2011) and possess hypotensive actions (Eno et al 2000) which are in agreement with their vasorelaxant effects (Runnie et al 2004). …”
Section: Discussionmentioning
confidence: 86%
“…There are also preliminary studies reporting its blood pressure lowering and vasodilatory properties. However, the possible models of actions of cardiovascular activities are lacking (38). It is known that oxidative stresses, such as generation of damaging reactive oxygen species, will lead to cell death under ischemic condition.…”
Section: Discussionmentioning
confidence: 99%
“…citratus is used throughout many regions of the world as a medicinal plant. It has been claimed to be effective in reducing fever, infection, rheumatism, headaches and abdominal discomfort, as well as acting as sedative, analgesic, anti-inflammatory, antispasmodic, diuretic, carminative and antihypertensive agents (Borrelli and Izzo, 2000;Runnie et al, 2004).…”
Section: Citratus (Lemongrass) Is a Tropical Perennial Herb And Ismentioning
confidence: 99%